Extending Democracy to Corporate Governance and Beyond: a Theory of Popular Economic Sovereignty - E. L. Rubin (Russian Journal of Economics and Law)
Objective: to carry out a comprehensive analysis of the impact of democratic governance principles in a state on corporate governance.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the following research methods: formal-logical and sociological.Results: the article proposes a different rationale for corporate democracy based on an equivalence, not an analogy. The equivalence is that subordination feels essentially the same to an individual whether a public or a private entity carries it out. In the political system, democracy counteracts subordination by giving everyone political autonomy, an independent voice in controlling the power structure. By the same reasoning, those who work for a living should arguably control the institutions for which they work. Thus, the norms of democracy, when translated into the economic realm, yield the principle that people should not work for their livelihood on terms another person establishes. This can be called the principle of popular economic sovereignty.Scientific novelty: for the first time, the work makes a conclusion that the modern understanding of both the state and the corporation developed from medieval corporativist thinking. This same mode of thought generated the idea of representation that enabled individuals who were not leaders of a structured hierarchy to participate in state decisions, certainly one of the great insights of Western political thought. Representation became the mechanism by which democratic government was instituted. As democracy developed, the scope of representation expanded to include all competent adults. This same expanded concept of representation can be extended to employment relations and would serve the same purposes as it serves in the political arena – individual autonomy and opposition to oppression. Corporations would be controlled by boards elected by the workers; small employers and individuals would be required to hire employees from labor exchanges run by the workers who are being provided. This proposal, although it sounds radical and impractical, could rather easily be implemented for both major corporations and all other employment relationships as well, and might well be more economically efficient than current modes of economic organization, as well as being more fair to the workers.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering the issues related to the theory of popular economic sovereignty.